2020
DOI: 10.1136/tobaccocontrol-2019-055554
|View full text |Cite
|
Sign up to set email alerts
|

Public support for cigarette price increase in Indonesia

Abstract: BackgroundThe current tobacco control policies in Indonesia are known to be ineffective in reducing tobacco consumption. Therefore, increasing cigarette prices is one of the effective instruments that should be supported by governments and society. This study aims to assess public support for cigarette price increases as well as to generate scientific evidence for the government and policymakers.MethodThis cross-sectional survey obtained data through telephone interviews with 1000 respondents aged ≥18 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus, they do not sell cigarettes in retail if the buyer is not over 18 years. 26 Research has demonstrated a noteworthy correlation between outdoor exposure to smoke in public areas and onset of smoking behavior among teenagers in Indonesia. According to research findings, adolescents who are exposed to secondhand smoke in public places outside closed spaces are found to have a higher risk of starting smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they do not sell cigarettes in retail if the buyer is not over 18 years. 26 Research has demonstrated a noteworthy correlation between outdoor exposure to smoke in public areas and onset of smoking behavior among teenagers in Indonesia. According to research findings, adolescents who are exposed to secondhand smoke in public places outside closed spaces are found to have a higher risk of starting smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Health Believe Model Concept [26] The Indonesian government needs to increase its political will to control tobacco consumption in Indonesia. Until now, tobacco control efforts in Indonesia have been ineffective [27]. The government must sign the Framework Convention on Tobacco Control (FCTC) to maximize the impact of the tobacco control program and make it more aligned with the guidelines given by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for choosing these diverse commodities as the focus of the study is to investigate the political economy in light of their distinct attributes and characteristics. Furthermore, our focus is exclusively on the sub-national level, as there is an abundance of evidence regarding the political economy of health taxation in Indonesia at the national level (20,21,23,(36)(37)(38)(39). The next section will describe the methodology and analytical approach used in this study, followed by results, and finally discussion and future recommendation.…”
Section: The Current Status Of Health Tax Implementation In Indonesiamentioning
confidence: 99%